Socioeconomic and substance use changes in emerging adults and their relationship with mood disorders in a population-based cohort - Farias, Clarisse de Azambuja; Cardoso, Taiane de Azevedo; Silva, Marielle Moro da; D’Angelo, Francesca; Mondin, Thaise Campos; Souza, Luciano Dias de Mattos; Silva, Ricardo Azevedo da; Kapczinski, Flavio; Jansen, Karen; Magalhães, Pedro V. S. (Frontiers in Psychiatry, 2022)
In this report, we aim to assess the interaction of bipolar disorder and major depressive disorder with the evolution of social roles, economic classification, and substance misuse in emerging adults. This is a longitudinal population-based study (n = 231 at baseline), in which participants were reassessed at a mean of 5 years after baseline. A structured clinical interview was used to diagnose the participants with bipolar disorder and major depression; a control group without mood disorders was included. Men with mood disorders were less likely to be married in the beginning of the study and less likely to work in the follow-up. Women with major depression were less likely to study and more likely to be in a lower economic class at the beginning of the study. In comparison, women with bipolar disorder were less likely to live with their parents and more likely to live with their children in the first wave of the study. Substance misuse was more likely in people with mood disorders, especially in men, and women with bipolar disorder had the highest likelihood in the follow-up. Albeit longitudinal analyses were limited by a possibly insufficient sample size and mediating mechanisms for change, such as stigma, were not explored, the study suggests sex-related specificities regarding change in social roles and substance use in people with mood disorders. Emerging adults, especially those with mood disorders, are in a period of change and instability, and at a greater risk for substance use and abuse.